1996
DOI: 10.1016/s0016-5085(96)70027-6
|View full text |Cite
|
Sign up to set email alerts
|

Regrowth of the rat biliary tree after 70% partial hepatectomy is coupled to increased secretin-induced ductal secretion

Abstract: After partial hepatectomy, the increase in secretin-induced ductal bile secretion observed during bile duct renewal results from proliferation of remaining cholangiocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

11
280
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 133 publications
(293 citation statements)
references
References 13 publications
11
280
1
1
Order By: Relevance
“…2,[5][6][7][8][9][10][11] For example, secretin enhances ductal secretory activity by interaction with specific receptors on cholangiocytes, 12 resulting in an increase in intracellular adenosine 3Ј,5Ј-monophosphate (cAMP) levels. [5][6][7]9,13,14 Increased cAMP levels induce the opening of Cl Ϫ channels and activation of the Cl Ϫ /HCO 3 Ϫ exchanger activity, which results in the secretin-induced bicarbonate-rich choleresis in vivo. [5][6][7]10,11,15 We have demonstrated that intrahepatic cholangiocytes are morphologically and functionally heterogeneous.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…2,[5][6][7][8][9][10][11] For example, secretin enhances ductal secretory activity by interaction with specific receptors on cholangiocytes, 12 resulting in an increase in intracellular adenosine 3Ј,5Ј-monophosphate (cAMP) levels. [5][6][7]9,13,14 Increased cAMP levels induce the opening of Cl Ϫ channels and activation of the Cl Ϫ /HCO 3 Ϫ exchanger activity, which results in the secretin-induced bicarbonate-rich choleresis in vivo. [5][6][7]10,11,15 We have demonstrated that intrahepatic cholangiocytes are morphologically and functionally heterogeneous.…”
mentioning
confidence: 99%
“…6,11,18 However, cholangiocytes markedly proliferate in response to specific pathological stimuli/toxins. 2,6,10,11,[18][19][20][21][22][23] Cholangiocyte proliferation is closely associated with in-creased DNA synthesis, which leads to increased ductal hyperplasia. 2,6,10,11 Different patterns of cholangiocyte proliferation exist.…”
mentioning
confidence: 99%
See 3 more Smart Citations